Detection of Light: From the Ultraviolet to the Submillimeter - Rieke, George (Cambridge University Press, 2002)
Detection of Light provides a comprehensive overview of the important approaches to photon detection from the ultraviolet to the submillimeter spectral regions. This expanded and fully updated second edition discusses recently introduced types of detector such as superconducting tunnel junctions, hot electron bolometer mixers, and fully depleted CCDs, and also includes historically important devices such as photographic plates. Material from many disciplines is combined into a comprehensive and unified treatment of the detection of light, with emphasis on the underlying physical principles. Chapters have been thoroughly reorganised to make the book easier to use, and each includes problems with solutions as appropriate. This self-contained text assumes only an undergraduate level of physics, and develops understanding as it is needed. It is suitable for advanced undergraduate and graduate students, and will provide a valuable reference for professionals in astronomy, engineering and physics.